The Influence of Work Stress, Workload and Work Environment on Nurse Performance at Elim Rantepao Hospital - Subba, Maria; pabisangan, jemi; Biringkanae, Astriwati (Yayasan Sinergi Kawula Muda, 2025)
The influence of work stress, workload and work environment on nurse performance at Elim Rantepao Hospital, North Toraja Regency5. This study aims to determine the influence of work stress, workload and work environment on nurse performance at Elim Rantepao Hospital. The population in this study were nurses at Elim Rantepao Hospital. The sampling technique used the Slovin formula so that 64 samples were obtained. The data analysis technique used was multiple linear regression analysis. The analysis tool used was the SPSS application. The results of the study showed that partially work stress and workload did not significantly affect nurse performance, the work environment partially had a significant effect on nurse performance and simultaneously work stress, workload and work environment affected nurse performance at Elim Rantepao Hospital, North Toraja Regency.